2008
DOI: 10.1590/s0004-282x2008000100011
|View full text |Cite
|
Sign up to set email alerts
|

Unusual dissemination patterns of low-grade astrocytomas in childhood

Abstract: -Context: Low-grade astrocytomas are intracerebral lesions of relatively high frequency in the under-18 pediatric population. They often present indolent behaviour, and complete surgical resection is the choice treatment. In cases where the surgery is not possible, chemotherapy and radiotherapy may be used. Medical reports do not recommend examination of the spinal cord at diagnosis or during treatment, since the risk of dissemination of the lesion to the spine is minimal according to medical experience. We de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…Although CSF dissemination has occasionally been reported in children with malignant gliomas 8 and more rarely in children with low-grade gliomas 18 (especially in brainstem gliomas), 12 LMSS is an exceptional complication in supratentorial DLGGs in adults.…”
Section: Discussionmentioning
confidence: 98%
“…Although CSF dissemination has occasionally been reported in children with malignant gliomas 8 and more rarely in children with low-grade gliomas 18 (especially in brainstem gliomas), 12 LMSS is an exceptional complication in supratentorial DLGGs in adults.…”
Section: Discussionmentioning
confidence: 98%
“…leptomeningeal dissemination of low-grade astrocytoma, particularly those diagnosed at presentation, has rarely been reported in the medical literature with fewer than 60 cases (3,6). The exact incidence still remains unclear (6,12). Previous studies have demonstrated that leptomeningeal dissemination occurs in approximately 4 to up to 12% of patients with low grade gliomas or low grade astrocytomas (9,11).…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanism and risk factors of leptomeningeal dissemination of low-grade PA is unknown (6,12). Recent studies cite intracranial surgical intervention (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations